Blended dried bakery product in swine starter rations - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1977)
A growth trial, a digestion trial, and a preference trial were conducted to evaluate a blended dried bakery product (BDBP) as an ingredient in swine starter rations. Replacing 0, 10, 20, or 30% corn with BDBP had no effect on average daily gain or feed efficiency. When given a choice, pigs preferred a ration containing 20% BDBP. The energy and protein digestibilities in BOBP were 91.5% and 87.88%, respectively.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Blended dried bakery product (BDBP); Ratioins; Protein digestibilities